PERANCANGAN GAME EDUKASI BELAJAR BAHASA INGGRIS MENGGUNAKAN ADOBE FLASH UNTUK TK ASSAKINAH WIROSARI GROBOGAN (Information Technology and Telematics, 2013)
A Game is media of learning nowadays because human beings have fundamental nature more quckly learn everything in visual-vebasl, so the game is is also good if involved in the educational process. application made learning materials interactively present with animation, text and sound. The application development aims to apply a form of multimedia based learning media animation in english language courses for kindergarten using Adobe Flash CS5 software. This application is intended for student TK Assakinah. The making of the application of this study can be used as a means of learning the english language subject specifically for children aged 4-6 years.Keyword : Educational games, English language for kindergarten, Adobe flash CS5